Linked Data Based Power Grid Management - Zdraveski, Vladimir; Trajanov, Dimitar; Kocarev, Ljupcho (My University, 2020)
A data model for a power delivery system is developed in this work, that combines the power grid data with the general geopolitical and socio-economical data from web and data hubs. It is based on the power grid ontology, that covers the required entities and connection properties for topology and measurements annotation in a power system. In order to proof the proposed model, several data queries and reports are presented and evaluated on recently published data sets. Few end-user tools are conceptually explored in order to note the usability for power companies as well as citizens.
Keywords: power grid, ontology, query, monitoring